Analysis algebraic system of arguments for prime size DHT - Prots’ko, Ihor (Видавництво Львівської політехніки, 2012)
Arguments of discrete harmonic transforms (DHT) for prime size specifying partial case of algebraic systems - abel groups is analyzed. Features of generate elements this algebraic systems are determined.
Keywords: algebraic systems; cyclic group; primitive elements; arguments; discrete harmonic transforms